Net benefit of smaller human populations to environmental integrity and individual health and wellbeing - Saraswati, Chitra Maharani; Judge, Melinda A.; Weeda, Lewis J. Z.; Bassat, Quique; Prata, Ndola; Le Souëf, Peter N.; Bradshaw, Corey J. A. (Frontiers in Public Health, 2024)
Introduction: The global human population is still growing such that our collective enterprise is driving environmental catastrophe. Despite a decline in average population growth rate, we are still experiencing the highest annual increase of global human population size in the history of our species — averaging an additional 84 million people per year since 1990. No review to date has accumulated the available evidence describing the associations between increasing population and environmental decline, nor solutions for mitigating the problems arising. Methods: We summarise the available evidence of the relationships between human population size and growth and environmental integrity, human prosperity and well-being, and climate change. We used PubMed, Google Scholar, and Web of Science to identify all relevant peer-reviewed and grey-literature sources examining the consequences of human population size and growth on the biosphere. We reviewed papers describing and quantifying the risks associated with population growth, especially relating to climate change. Results: These risks are global in scale, such as greenhouse-gas emissions, climate disruption, pollution, loss of biodiversity, and spread of disease — all potentially catastrophic for human standards of living, health, and general well-being. The trends increasing the risks of global population growth are country development, demographics, maternal education, access to family planning, and child and maternal health. Conclusion: Support for nations still going through a demographic transition is required to ensure progress occurs within planetary boundaries and promotes equity and human rights. Ensuring the well-being for all under this aim itself will lower population growth and further promote environmental sustainability.